Preparing Sm2Fe17Cx compound by high-energy ball-milling Sm-Fe alloy in heptane followed by annealing, re-milling and re-annealing. (5th December 2016) - Geng, Hongmin; Ji, Yuan; Feng, Xueyuan; Zhang, Jingjing; Gao, Yuchao; Yan, Yu; Wang, Wenquan; Su, Feng; Du, Xiaobo
Abstract: In this paper, we present a new preparation method for Sm2 Fe17 Cx compound based on solid-liquid reaction. High-energy ball-milled in heptane for 8 h, Sm25 Fe75 alloy containing SmFe2, SmFe3 and Sm2 Fe17 phases disproportionates into SmH2 + δ, α-Fe, Fe3 C and graphite. H and C atoms come from heptane. Annealed to 850 °C under vacuum, SmH2 + δ decomposes and Sm-C, Sm2 Fe14 C, α-Fe are formed. Re-milling for 1.5 h in argon and re-annealing at 600 °C for 15 min promotes the transformation of partial Sm2 Fe14 C to Sm2 Fe17 Cx ( x : 0.3–1.5) and the formation of nanoscale microstructure. Due to the intergrain exchange coupling between magnetically hard Sm2 Fe17 Cx and soft Sm2 Fe14 C/α-Fe, the product behaves like magnet with single magnetically hard phase. Maximum coercivity of 4.4 kOe is obtained. Shorter ball-milling time (6 h) results in the insufficiency of α-Fe and Fe3 C, limiting the formation of Sm2 Fe14 C and the transformation of Sm2 Fe14 C to Sm2 Fe17 Cx . Longer ball-milling time (10 h) results in excess of α-Fe in the final product. Both cases reduce the ratio of magnetically hard phase to soft one in the nanocomposite magnet, resulting in the decrease of coercivity. Graphical abstract: Highlights: High-energy ball-milled in heptane, Sm-Fe alloy disproportionates into SmH2 + δ, α-Fe and Fe3 C. Heated to 850 °C in vacuum, SmH2 + δ decomposes and magnetically soft Sm2 Fe14 C phase is formed. The H and C atoms come from the decomposition of heptane. Re-milled in argon and re-annealed at 600 °C under vacuum for 15 min, magnetically hard Sm2 Fe17 Cx ( x = 0.3–1.5) is formed.